Information Seeking and MSM's Beliefs about PrEP and Condoms. Issue 7 (7th June 2022) - Schwartz, Joseph; Grimm, Josh; Zimmerman, Rick; Clement, Meredith
ABSTRACT: This study examined how frequently men who have sex with men (MSM) used a selection of sources, including news media, social media, health organizations, and dating/hookup apps, for HIV information. Additionally, the study explored the extent to which MSM's efficacy beliefs about pre-exposure prophylaxis (PrEP) and perceptions of condom importance could be predicted by the sources they used. A sample of MSM ( N = 969) were surveyed online. Results showed that respondents obtained information about HIV most often from HIV organizations, LGBT organizations, and dating/hookup apps, particularly the apps Growlr, Scruff, and Grindr. Use of the app Scruff was the strongest source-based predictor of beliefs about both PrEP and condoms. Implications for health promotion are discussed.